Multipliers in Holomorphic Mean Lipschitz Spaces on the Unit Ball. (21st June 2012) - Cho, Hong Rae
Abstract : For 1 ≤ p ≤ ∞ and s > 0, let Λ s p be holomorphic mean Lipschitz spaces on the unit ball in ℂ n . It is shown that, if s > n / p, the space Λ s p is a multiplicative algebra. If s > n / p, then the space Λ s p is not a multiplicative algebra. We give some sufficient conditions for a holomorphic function to be a pointwise multiplier of Λ n / p p .